2020
DOI: 10.3389/fnagi.2020.602688
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Activation and Neuronal Differentiation of Lgr5+ Basal Cells in Injured Olfactory Epithelium via Notch Signaling Pathway

Abstract: Aging is an important factor affecting function of smell, leading to the degeneration of mature olfactory sensory neurons and inducing the occurrence of smell loss. The mammalian olfactory epithelium (OE) can regenerate when subjected to chemical assaults. However, this capacity is not limitless. Inactivation of globose basal cells and failure to generate sensory neurons are the main obstacles to prevent the OE regeneration. Here, we found the significant attenuation in mature sensory neuronal generation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Olfactory neurospheroids can serve as models of schizophrenia 192 , autism spectrum disorder (ASD) 193 and Parkinson disease 194 . In addition, bioprinted scaffold-based models 195 and organoid models of the olfactory epithelium are being explored 196 , 197 .…”
Section: Region-specific Cns Modelsmentioning
confidence: 99%
“…Olfactory neurospheroids can serve as models of schizophrenia 192 , autism spectrum disorder (ASD) 193 and Parkinson disease 194 . In addition, bioprinted scaffold-based models 195 and organoid models of the olfactory epithelium are being explored 196 , 197 .…”
Section: Region-specific Cns Modelsmentioning
confidence: 99%
“…Wnt signaling can promote the proliferation of Lgr5+ GBCs and regeneration of olfactory neurons. 10 , 11 Li et al used a strain a strain that destroyed the function of endogenous Lgr5 gene to characterize Sox2 expression in GBCs under normal conditions and in a lesion-regeneration model. They showed that a lack of Sox2 expression reduced the proportion of natural ORNs significantly.…”
Section: Research Progress In the Mechanism Of On Regenerationmentioning
confidence: 99%
“…Lgr5 also labels stem and progenitor cells in sensory organs such as eye [33], ear [33][34][35], and tongue [36]. In nose, Lgr5 marks the GBCs located in the OE and functions in the recovery of injured OE [37][38][39]. However, how Lgr5 + cells behave in the homeostasis and regeneration of OE is still not very clear.…”
Section: Introductionmentioning
confidence: 99%